The proposal (2009) [videorecording (DVD)] - Fletcher, Anne, 1966-; Bullock, Sandra; Reynolds, Ryan; Akerman, Malin, 1978-; Nelson, Craig T.; Steenburgen, Mary (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2009)
High-powered book editor Maggie is everyone's worst nightmare: ruthless, driven, and tactless. When she finds herself faced with deportation back to Canada, she coerces her much younger assistant into marrying her. However, when the government becomes suspicious, they embark upon a charade in order to make the marriage seem legitimate.